Realism, Philosophy and Social Science - Dean, K. author. aut Link
VI, 199 p.
Keywords: The authors examine the relationship between social science and philosophy and ask what sort of work social science and an accompanying philosophy should do. They reintroduce the question of ontology, through the work of Roy Bhaskar. The book argues against philosophising and is committed to a philosophical approach grounded in the social sciences.